2012
DOI: 10.4161/biom.23246
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of cryoprotectants on the porosity and stability of insulin-loaded PLGA nanoparticles after freeze-drying

Abstract: PLGA nanoparticles are useful to protect and deliver proteins in a localized or targeted manner, with a long-term systemic delivery pattern intended to last for a period of time, depending on polymer bioerosion and biodegradability. However, the principal concern regarding these carriers is the hydrolytic instability of polymer in aqueous suspension. Freeze-drying is a commonly used method to stabilize nanoparticles, and cryoprotectants may be also used, to even increase its physical stability. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 34 publications
(35 reference statements)
3
85
0
1
Order By: Relevance
“…Alternatively, the use of sonication as the source of agitation to form the two emulsion types preserves the physical and chemical stability of insulin during NP fabrication (Fonte et al, 2012;Sarmento et al, 2007;Sheshala et al, 2009). However, low encapsulation efficiency (Sarmento et al, 2007;Sheshala et al, 2009) and high initial burst effect (Fonte et al, 2012;Ibrahim et al, 2005) are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the use of sonication as the source of agitation to form the two emulsion types preserves the physical and chemical stability of insulin during NP fabrication (Fonte et al, 2012;Sarmento et al, 2007;Sheshala et al, 2009). However, low encapsulation efficiency (Sarmento et al, 2007;Sheshala et al, 2009) and high initial burst effect (Fonte et al, 2012;Ibrahim et al, 2005) are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 92%-94% of FB amount was released in the first 10 hours from FD-NPsTRE and IR-NPsTRE, respectively, as shown in Figure 1C and D. TRE was reported as a protectant agent that induces or increases the porosity of NPs. 39 It may open a pathway for a faster FB release from NPs and for its possible degradation by external factors. Two mechanisms of pore formation have been postulated, and it is probable that both contribute to the higher FB release rate.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…[103] Thus, Fonte et al suggested the lyophilization of PLGA nanoparticles to improve the long-term stability, reducing the instability of protein-loaded PLGA nanoparticles formulations. [104] However, to reduce the aggregation of PLGA nanoparticles and physical stress caused by ice crystals, lyoprotectants should be added to PLGA nanoparticles formulations. Fonte et al studied the influence of 5 different lyoprotectants in insulin-loaded PLGA nanoparticles stability after lyophilization.…”
Section: Poly(lactic-co-glycolic) Acid Nanoparticlesmentioning
confidence: 99%